2017
DOI: 10.1111/jch.13076
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of a new algorithm to detect atrial fibrillation in a home blood pressure monitor

Abstract: The authors evaluated a new algorithm for detecting atrial fibrillation (AF) using a home blood pressure monitor. Three serial blood pressure values were measured by the monitor in 16 patients with AF and 20 patients with sinus rhythm. The authors defined "monitor AF in irregular pulse peak (IPP) 25" as follows: (1) IPP: |interval of pulse peak − the average of the interval of the pulse peak| ≥ the average of the interval of the pulse peak ×25%; (2) irregular heart beat: beats of IPP ≥ total pulse ×20%; and (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…The association between the pulse wave of the wrist‐type monitor and the RR duration of ECG was good. We previously confirmed the diagnostic value of the AF algorithm using a home blood pressure monitor, and here we found that pulse wave analysis using the wrist‐type monitor also had good diagnostic value for AF. The wrist‐type monitor is mobile and easy to carry.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The association between the pulse wave of the wrist‐type monitor and the RR duration of ECG was good. We previously confirmed the diagnostic value of the AF algorithm using a home blood pressure monitor, and here we found that pulse wave analysis using the wrist‐type monitor also had good diagnostic value for AF. The wrist‐type monitor is mobile and easy to carry.…”
Section: Discussionsupporting
confidence: 84%
“…The interval of pulse waves was analyzed, and the average pulse wave interval was calculated in 6 measurements (3 measurements each for the left and right wrist). We defined “monitor AF in irregular pulse peak (IPP) 15/20/25” as follows: (a) IPP: |interval of pulse wave – the average of the interval of the pulse wave| ≥ the average of the interval of the pulse wave × 15/20/25%; (b) irregular heartbeat (IHB): beats of IPP ≥ total pulse × 20%; and (c) the “monitor AF (IPP 15/20/25)”: ≥ 4 IHBs of the six pulse wave measurements according to a past report …”
Section: Methodsmentioning
confidence: 99%
“…In this issue of the Journal, Kabutoya and colleagues reported a new algorithm for the detection of AF using a BP monitor. The authors believe that the new algorithm may further improve accuracy for the detection of AF during BP measurement.…”
Section: Studies On the Diagnostic Accuracy Of Automated Blood Pressumentioning
confidence: 99%
“…The new algorithm was developed from a new angle to improve specificity in the detection of AF. However, cardiac arrhythmias other than AF were not included in this study . Both the current and previous algorithms were designed by assessing pulse rate irregularity.…”
Section: Studies On the Diagnostic Accuracy Of Automated Blood Pressumentioning
confidence: 99%
“…AF itself is associated with increased risk of stroke and systemic emboli, but patients with both AF and hypertension have a higher risk of stroke compared to those with either condition alone . Thus, earlier detection and treatment of new‐onset AF are essential in patients with hypertension …”
Section: Introductionmentioning
confidence: 99%